2019
DOI: 10.18502/ijm.v11i5.1959
|View full text |Cite
|
Sign up to set email alerts
|

Improves in external and internal egg quality of Japanese quail (Coturnix coturnix japonica) by giving lactic acid bacteria as alternative antibiotic growth promoter

Abstract: Background and Objectives: An experiment was designed to determine the effect of using lactic acid bacteria as alternative antibiotic growth promoters on external and internal quality of egg’s Coturnix coturnix japonica. Materials and Methods: Coturnix coturnix japonica (n=240, 14 weeks of age) were randomly distributed into six treatment groups. The treatments were P0 (free antibiotic feed), P1 (free antibiotic feed with 1 gram antibiotic growth promoters (AGP)/100kg feed), P2 (free antibiotic feed with 5 gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…It has been reported previously that addition of selenium yeast in hen diets improved egg shape index in laying hens [39]. Whereas past researchers have found that supplementation of yeast and yeast cell wall improved Haugh unit [9,26], the present study has shown that addition of red yeast to hen diets improved Haugh unit, which is a major indicator of egg quality and freshness [40]. This implies that the supplementation of red yeast in hen diets can have beneficial effects on egg quality in laying hens.…”
Section: Discussioncontrasting
confidence: 50%
“…It has been reported previously that addition of selenium yeast in hen diets improved egg shape index in laying hens [39]. Whereas past researchers have found that supplementation of yeast and yeast cell wall improved Haugh unit [9,26], the present study has shown that addition of red yeast to hen diets improved Haugh unit, which is a major indicator of egg quality and freshness [40]. This implies that the supplementation of red yeast in hen diets can have beneficial effects on egg quality in laying hens.…”
Section: Discussioncontrasting
confidence: 50%
“…These results were in agreement with Ayasan et al (2006) who observed higher eggshell weight with probiotic treatment in laying Japanese quail. Furthermore, egg shell weight significantly ( P < 0.05) excelled that of the control, being 1.47 and 1.54 g for birds that received 10 g probiotic/200 L drinking water and 10 g probiotic/100 kg of feed, respectively ( Lokapirnasari et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…casei and L . rhamnosus could increase egg weight and improve yolk colour, albumen height and haugh unit (Lokapirnasari et al ., 2019 ). Recently, faecal microbiota transplantation (including L .…”
Section: Introductionmentioning
confidence: 99%
“…In avian, supplied laying hens with Bacillus subtilis could improve their egg production and eggshell quality (Abdelqader et al, 2013;Ribeiro et al, 2014). In Japanese quail, dietary supplementation with probiotics containing Lactobacillus (L.) casei and L. rhamnosus could increase egg weight and improve yolk colour, albumen height and haugh unit (Lokapirnasari et al, 2019). Recently, faecal microbiota transplantation (including L. frumenti, L. gasseri) from a Chinese native pig breed to early weaning piglets was demonstrated to prevent weaning stress-induced diarrhoea (Hu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%